Preparation And Characterization Of Polylactic Acid/ Polycaprolactone/ Modified Clay Composites - Hoidy, Wisam H. (2010)

(untitled)
In this study, synthesis and characterisation of fatty hydroxamic acid (FHA) from palm olein with hydroxylamine using reflux method. FTIR spectrum, 1H NMR and elemental analysis tests conducted on FHA reveal that FHA was successfully produced from palm olein,. The conversion percentage of palm olein to FHA increases (81%) when the optimum reaction time to be 10 hours and a molar ratio of (hydroxylamine to palm olein) 7:1. FHA was used as one of the organic compounds to modify natural clay (Na-MMT). The clay modification was carried out by stirring the clay particles in an aqueous solution of the FHA or octadecylammonium (ODA) by which the clay layer distance increases from 12.2 Å to 31.02 Å and 29.49 Å, respectively. The modified clays were then used in the preparation of polylactic acid/polycaprolactone (PLA/PCL) composites. The optimum clay contents that yielded maximum tensile strength were 2% and 3% for PLA/PCL-ODA-MMT and PLA/PCL-FHA-MMT, respectively. The intercalation of the modifier in the clay layer was characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA) and Fourier Transform Infrared (FTIR). Elemental analysis (CHN) was used to estimate the amount of FHAs and ODA in the clay. In the first part of the preparation, the composites were synthesized by melt blending of the modified clay and PLA/PCL by a two-roll-mill internal mixer blending at a temperature setting of 185°C, rotor speed of 50 rpm and the mixing time of 12 minutes. Mechanical properties of the produced composites were then characterized by an lnstron universal testing machine. The composites were also synthesized by using solution casting in the second part of the study. In this process, Chloroform was chosen to dissolve PLA and PCL under magnetic stirrer for 1 h. The required amount of the modified clay was added to the mixture, the composites were poured into Petri dish and left to dry. The results indicate that the presence of the modified clay has dramatically improved the properties. Both of PLA/PCL-ODA-MMT and PLA/PCL-FHA-MMT composites prepared by melt blending have high tensile strength 38.91 MPa and 39.31 MPa compared to those of solution casting 31.43 MPa and 32.84 MPa for PLA/PCL-ODA-MMT and PLA/PCL-FHA-MMT, respectively. These composites were further characterized by XRD, FTIR, TGA and scanning electron microscopy (SEM).It was found that similar results of FTIR and TGA were obtained when solution casting and melt blending processes were used to produce PLA/PCL, PLA/PCLODA- MMT and PLA/PCL-FHA-MMT. Thermal stability of these composites was improved to 349.26 °C and 354.62 °C for PLA/PCL-ODA-MMT and PLA/PCLFHA- MMT, respectively, compared with the blend of polymers 342.15 °C. While the values of basal spacing in melt blending were higher 34.61 Å and 36.15 Å compare with those of solution casting 31.15 Å and 33.18 Å for PLA/PCL-ODA-MMT and PLA/PCL-FHA-MMT, respectively.